Fireless cooking - Withington, Charles Hall (My University, 1906)
Introduction: Military life being one of exposure and activity the soldiers food must be adequate to repair the ordinary wear and tear, as well as to supply energy and animal heat. The problem then is to procure the proper kind or food properly prepared, since a military diet must not only be nutritious but palatable. Food may be divided into two great classes: 1st. Inorganic: as water, salt, etc. 2nd. Organic: which is sub-divided into three groups. a. Nitrogenous: meats, eggs, etc. b. Carbohydrates: starches, sugars, etc. c. Fats and Oils. On the principle that food is to supply energy and animal heat as well as replace the wasted tissues of the body it is considered by authorities on foods that the nitrates and carbohydrates are the most essential in quantity the others, water excepted, being necessary only in such small quantities that they may be termed condiments. The meats, eggs, and legumes furnish the greatest amount of nitrates, the legumes also being very rich in carbohydrates. The preparation of these foods is accomplished by what is termed cooking, which consists in sore forms of applying heat to food. The cooking temperature or different kinds of food to preserve their most nutritious qualities varies. It is found by experience that foods containing the most nitrates preserve their most nutritive qualities when cooked at a temperature or 180° F. By what process of cooking can we best do this, and at the same time make them easy for assimilation, attractive, and palatable? Many kinds of apparatus have been invented in the last century for cooking at this temperature, by the retention or heat. The principle of cooking by the retention of heat is an old one, and has been used for many years in a primitive form by the people of Norway and Germany, and also by the Indians or New Mexico. About 30 years ago it was tried in the British Army but soon dropped into disuse. It has been left to the genius and perseverance of the Yankee, to perfect the method of what is known as fireless cooking.
Citation: Withington, Charles Hall. Fireless cooking. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Home Economics; Fireless Cookery; Military; Theses